PENGARUH KONFLIK PERAN GANDA DAN STRESS KERJA TERHADAP KINERJA PERAWAT WANITA RUMAH SAKIT MUHAMMADIYAH GRESIK - NURUL HUDALIFAH (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
This study aims to test that Work-Family Conflict and Job Stress on Performance Women's Hospital Nurses Muhammadiyah Gresik. By using a sample of 36 respondents. Testing is done by using multiple regression analysis. The results of multiple regression showed that Work-Family Conflict and Job Stress significant effect on Nurse Performance Female